Emerging and Young Adulthood : Multiple Perspectives, Diverse Narratives - Konstam, Varda (Advancing Responsible Adolescent Development, 2015)
This data-rich volume offers new insights into the transitional period between adolescence and adulthood. It analyzes core concepts typically associated with adolescence, such as identity development, emerging sexuality, deepening relationships, and exploration of career choices as individuals age into their twenties and early thirties. Chapters examine the challenges of self-exploration, responsibilities, and independence as this generation approaches adulthood with deliberation in an uncertain world with vastly different perspectives from that of their parents. And in the tradition of its predecessor, the book's first-person excerpts emphasize and illuminate the diversity of the population and its stakeholders, including parents and employers. Each chapter is updated and revised to reflect the current literature that has evolved since the first edition was published. Additional chapters address two increasingly important areas of interest: the virtual life of the emerging and young adult; and the career-related challenges emerging and young adults encounter in their search for a vocational home. Rich additional narratives serve to elucidate the terrain emerging and young adults encounter as they begin to establish themselves in the world of work and social and romantic relationships. Key areas of coverage include:  Identity formation in environmental context Culture: opening paths, creating detours The "tyranny" of choice: re-examining the prevailing narrative Examination of career paths for emerging and young adults Emotional and social lives of emerging and young adults Overlapping and disparate views of employers Mental health issues of emerging and young adults The Second Edition of Emerging and Young Adulthood is essential reading for researchers, clinicians, therapists and other professionals, and graduate students in developmental, school, and counseling psychology and related social and behavioral sciences.